Efeitos de animacidade do antecedente na resolução de pronomes sujeito - Morgado, Sara; Luegi, Paula; Lobo, Maria (Revista da Associação Portuguesa de Linguística, 2018)
We report two experiments, a self-paced reading task and an off-line questionnaire, that tested if the overt subject pronoun in European Portuguese was sensitive to the animacy (animate vs. inanimate) of the antecedent in object position. We found higher reading times when the overt pronoun was forced to retrieve an inanimate antecedent compared to retrieving an animate one (Experiment 1) and less object choices with inanimate antecedents (compared to animate ones). Our findings show that several factors are taken into account during the resolution of pronominal forms, including animacy features, favouring thus a multifactorial approach to pronoun retrieval (Kaiser & Trueswell, 2008). We propose that there is a hierarchy that considers both syntactic and semantic information in pronoun resolution and that within the syntactic information the prominence of entities varies according to their animacy features. Our results are neither explained by processing theories that only consider syntactic factors (Carminati, 2005), nor by theoretical accounts that associate strong pronouns with animacy features (Cardinaletti & Starke, 1999).